Compliance with Clinical Pathway for Cesarean Section Before and After the Implementation of JKN in Hospital X - Nurwahyuni, A; Sjaaf, A C; Puspa Hapsari, W; Nugraha, R R (KnE Life Sciences, 2018)
Hospital X, which is a Class-A hospital in Jakarta, had set and implemented Clinical Pathway for cesarean section before 2012. During its implementation, the analysis of service providers’ compliance to the clinical pathway has never been done. With the implementation of JKN, the adherence to clinical pathway was expected to increase. This study aimed to compare compliance to the clinical pathway before and after JKN. The sample of this cross-sectional study with quantitative approach takes all Caesarean Section cases without complication and comorbidity in 2012 and 2015, which consisted of 58 cases in 2012 and 117 cases in 2015, respectively. Patients Characteristics data, medical data (diagnosis and procedures) and details of services per patient were taken from hospital information system. Tools for pre-clinical pathway development and clinical pathway evaluation (clinpath v.2.0) were used to analyze the data. The results indicated that the average length of stay (LOS) in 2012 (3.8 day) were shorter compared to LOS in 2015 (4.5 days), while LOS in clinical pathway is 4 days. Variations of laboratory examination is also greater in 2015 as well as for the drug. Keywords: clinical pathway, healthcare service, hospital, caesarean section, variation